2009
DOI: 10.1603/008.102.0118
|View full text |Cite
|
Sign up to set email alerts
|

Dead Reckoning in Tunnel Propagation of the Formosan Subterranean Termite (Isoptera:Rhinotermitidae)

Abstract: Subterranean termites excavate extensive tunnel complexes in search of resources. The high energetic cost of digging through soil places stringent requirements on the efficiency of tunnel patterns for both search and transport at the time of their initial construction. An efficient spread of tunnels could result from simple diffusion away from a shared origin, but the ability to actively orient the burgeoning tunnels allows for the construction of efficient patterns when faced with the possibility of detours o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…For instance, Su and collaborators (2004) studied the galleries excavated by termites (Coptotermes formosanus and Reticulitermes flavipes) in a thin layer of sand and observed that in spite of being constrained to dig in two dimensions, the number of loops remained low, compared with what was produced in computer simulations of termite digging. In fact, specific digging 'rules' such as initiating new galleries at angles as large as possible from each other (Robson et al, 1995), or maintaining a digging direction oriented away from the point of initiation of the tunnel (Bardunias and Su, 2009), are mechanisms that also allow the appearance of loops to be minimised.…”
Section: A Variety Of Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Su and collaborators (2004) studied the galleries excavated by termites (Coptotermes formosanus and Reticulitermes flavipes) in a thin layer of sand and observed that in spite of being constrained to dig in two dimensions, the number of loops remained low, compared with what was produced in computer simulations of termite digging. In fact, specific digging 'rules' such as initiating new galleries at angles as large as possible from each other (Robson et al, 1995), or maintaining a digging direction oriented away from the point of initiation of the tunnel (Bardunias and Su, 2009), are mechanisms that also allow the appearance of loops to be minimised.…”
Section: A Variety Of Formsmentioning
confidence: 99%
“…For instance, it is known that ants can rely on memory to return to the location of foraging sites (Sundström, 1993), and it seems plausible that they also rely on memory when returning to the location of a building or digging site. Digging termites can also integrate their moving direction, for instance to recover the overall direction of a gallery after encountering an obstacle (Bardunias and Su, 2009).…”
Section: Nest Building and The Coordination Of Individual Activitiesmentioning
confidence: 99%
“…The two sheets of plexiglass were held together with clips (Bardunias and Su, 2009a). A 5 mm diam hole was drilled in the center of the top sheet as an entry hole.…”
Section: Tunneling Assaysmentioning
confidence: 99%
“…One potential mechanism consists of initiating new galleries at angles as large as possible from each other [30]. Bardunias & Su [31] found that Coptotermes formosanus termites were able to maintain a digging direction oriented away from the point of initiation of the tunnel, a mechanism that also allows to minimize the appearance of cycles. A similar The frequently used measure of branching order [9] is also essentially a measure of topologic path length, which counts the number of bifurcations on the path from a given network location to a root node (usually represented by a nest).…”
Section: The Transportation Problemmentioning
confidence: 99%